Zinc manganate/manganic oxide bi-component nanorod as excellent cathode for zinc-ion battery. (15th March 2021) - Ma, Shi-Chao; Sun, Ming; Wang, Si-Xu; Li, Dong-Shuai; Liu, Wei-Liang; Ren, Man-Man; Kong, Fan-Gong; Wang, Shou-Juan; Xia, Yong-Mei
Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) have been receiving much attention because they are cheap, safe, and environment-friendly. However, their application is bottlenecked by limitation in high-capacity cathode and types of materials to achieve satisfactory cyclability. Therefore, developing new cathode materials for rechargeable zinc-ion batteries is essential. Herein, we report promising ZIBs based on metal-organic framework-derived 2-methylimidazole zinc salt (ZIF-8)/Mn2 O3 nanocomposites as cathode and zinc as the anode. ZnMn2 O4 /Mn2 O3 bi-component nanorods were synthesized by annealing ZIF-8/MnO2 precursors, which showed a reversible discharge capacity of 230 mAh g –1 at 100 mA g –1 after 120 cycles and a high capacity of 80 mAh g –1 at a large current density of 1000 mA g –1 . The superior zinc storage performance is attributed to the synergistic effect between ZnMn2 O4 and Mn2 O3 . Graphical abstract: Image, graphical abstract